Media use and Obesity in Sabah, Malaysia - Andreas Totu; Oswald Aisat Igau; Halina Sendera Mohd Yakin (2018)
This study explores the effects of media consumption, which are thought to be mostly sedentary in nature, towards the problem of obesity among youths in Sabah, Malaysia. This study surveyed 549 respondents from 12-19 years old categories from various secondary schools in Sabah, Malaysia. Some interesting findings of this study include the high preference among youths in Sabah to choose foods offered by franchised restaurants. It was also found that youths in Sabah are not active physically because most of their time was spent engaging with various forms of information and communication technology (ICT), particularly hand phone and computer. Excessive usage of media appears to replace the time for physical activities, which deprive them the chance to burn the calories absorbed from franchised restaurants‟ foods. Such situation was made worst when youths tend to consume unhealthy foods, such as snacks and crisps, when engaging with media. This indirect effect of media was also indicated in this study.